2021
DOI: 10.3389/fphar.2021.748852
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting Myc Interacting Proteins as a Winding Path in Cancer Therapy

Abstract: MYC, as a well-known oncogene, plays essential roles in promoting tumor occurrence, development, invasion and metastasis in many kinds of solid tumors and hematologic neoplasms. In tumors, the low expression and the short half-life of Myc are reversed, cause tumorigenesis. And proteins that directly interact with different Myc domains have exerted a significant impact in the process of Myc-driven carcinogenesis. Apart from affecting the transcription of Myc target genes, Myc interaction proteins also regulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 161 publications
(182 reference statements)
1
10
0
Order By: Relevance
“…In tumors, the low expression and short half-life of Myc can be reversed, which can lead to tumorigenesis. Proteins that directly interact with different Myc domains can affect the transcription of Myc target genes and regulate the stability of Myc through post-translational modifications, such as acetylation, methylation, and phosphorylation ( Zhou et al, 2021 ). In acute myeloid leukemia, Myc directly inhibits the expression of TFEB (a transcription factor regulated by mTORC1) and regulates DNA methylation and cell differentiation ( Wu and Eisenman, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In tumors, the low expression and short half-life of Myc can be reversed, which can lead to tumorigenesis. Proteins that directly interact with different Myc domains can affect the transcription of Myc target genes and regulate the stability of Myc through post-translational modifications, such as acetylation, methylation, and phosphorylation ( Zhou et al, 2021 ). In acute myeloid leukemia, Myc directly inhibits the expression of TFEB (a transcription factor regulated by mTORC1) and regulates DNA methylation and cell differentiation ( Wu and Eisenman, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The central domain consists of a proline-rich PEST segment, a calpain cleavage site (CAPN) responsible for cytosolic MYC partial cleavage of the C-terminus producing “MYC-nick”, and a nuclear localization sequence (NLS). Six highly conserved regions dubbed MYC homology boxes (MBs 0–IV) are sequentially distributed across TAD and the central domain, which bind to different MYC interactors and thus enable MYC to regulate distinct enzymatic reactions throughout the transcriptional process (Figure B) …”
Section: Biochemistry Of Mycmentioning
confidence: 99%
“…Six highly conserved regions dubbed MYC homology boxes (MBs 0−IV) are sequentially distributed across TAD and the central domain, which bind to different MYC interactors and thus enable MYC to regulate distinct enzymatic reactions throughout the transcriptional process (Figure 1B). 21 Proteomic profiling of the MB interactomes has revealed that half of the MYC interactors require one or more MBs for binding wherein two MBs, MB0 and MBII, are universally required for transformation. 22 It should be appreciated that the interactome MB0 accelerates the transcription process by binding to the general transcription factor IIF (TFIIF) and also recruits PP1 phosphatase via cofactors to regulate MYC activity and stability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…c-MYC is documented to be one of the most up-regulated oncogenes in different types of cancers [ 25 , 26 ]. c-MYC alteration has been reported in 9.92% of breast carcinoma patients [ 27 ].…”
Section: C-myc In Er+ve Breast Cancermentioning
confidence: 99%
“…In this manner, c-MYC can repress MIZ1 target genes; some of which belong to cell cycle inhibitors such as CDKN1A (p21) and CDKN2B (INK4B) [23,24]. c-MYC is documented to be one of the most up-regulated oncogenes in different types of cancers [25,26]. c-MYC alteration has been reported in 9.92% of breast carcinoma patients [27].…”
Section: C-myc In Er+ve Breast Cancermentioning
confidence: 99%